Effect of micronutrients on the risk of Graves’ disease: a Mendelian randomization study - Chen, Fangsen; Qiu, Rongliang; Lin, Zhiqing; Chen, Junhan; Liu, Peitian; Huang, Yanling (Frontiers in Nutrition, 2024)
Abstract Background: Micronutrient research on Graves’ disease (GD) is limited and controversial. Therefore, in order to explore possible correlations between genetically predicted amounts of six micronutrients (Copper (Cu), Iron (Ir), Zinc (Zn), Calcium (Ca), Vitamin C (VC) and Vitamin D (VD)) and GD risk, we carried out Mendelian randomization research (MR). Method: We conducted an MR analysis using genome-wide association studies (GWAS) from people of European ancestry and aggregated information from UK Biobank to provide insight into the relationships between micronutrients and GD. The causal link between exposure and outcome was tested using three different techniques: Inverse Variance Weighted (IVW), MR-Egger, and Weighted Median Estimator (WME). The heterogeneity of outcomes was also assessed using Cochran's Q statistic, and pleiotropy was assessed by MR-Egger intercept, MR-PRESSO. Result: IVW analyses showed evidence of no significant effect of genetically predicted micronutrient concentrations on GD, except for Cu. (Cu: OR = 1.183, P = 0.025; Ir: OR = 1.031, P = 0.794; Zn: OR = 1.072, P = 0.426; Ca: OR = 1.040, P = 0.679; VC: OR = 1.011, P = 0.491; VD: OR = 0.902, P = 0.436). Significant heterogeneity was observed in Ca and VD (Ca: Q = 264.2, P = 0.002; VD: Q = 141.42, P = 0.047). The MR-Egger intercept method identified horizontal pleiotropy between serum Ca levels and GD (MR-Egger intercept = -0.010, P = 0.030), with no similar findings for other micronutrients. Conclusions: MR analysis showed a possible causal relationship between the genetically predicted concentration of Cu and the risk of GD, whereas the genetically predicted concentrations of Ir, Zn, Ca, VC, and VD may not be causally related to the risk of GD.